Determinants and features of voluntary disclosure in the Chinese stock market - Yang Lan; Lili Wang; Xueyong Zhang (China Journal of Accounting Research, 2013)
This paper offers in-depth analysis of the determinants and features of voluntary disclosure based on information in the annual reports of 1066 Chinese firms listed on the Shanghai and Shenzhen Stock Exchanges. This extensive sample represents about 80% of all public companies in China. Our findings suggest that voluntary disclosure in China is positively related to firm size, leverage, assets-in-place, and return on equity and is negatively related to auditor type and the level of maturity or sophistication of the intermediary and legal environments. We also find some evidence to suggest a quadratic convex association between state ownership and voluntary disclosure. However, our analysis provides no evidence that extensive disclosure benefits public companies in China in the form of a lower cost of equity.
Keywords: G30; G32; G34; 650; Voluntary disclosure; Cost of equity; Ultimate control; Chinese stock market